Sierra Leone : Disarmament, Demobilization and Reintegration (DDR) - Bradley, Sean; Maughan, Philippe; Fusato, Massimo (2012)
This note describes the Disarmament and Demobilization (D&D) of combatants from all warring parties in January 2002, which marked the official end of the civil war in Sierra Leone. D&D was part of a larger disarmament, demobilization, and reintegration (DDR) program, implemented by the Government of Sierra Leone with the support of the World Bank, together with other international institutions and Nongovernmenal Organizations (NGOs). The experience of Sierra Leone is discussed, as well as, how the Bank can play a role in post-conflict transitions, complementing political and security efforts of client governments and the international community.